Architectural development in Lesotho - Hancock, Peter (School of Architecture, Planning and Geomatics, 2026)
Having been actively engaged professionally in architectural development in Lesotho since 1961, the author has had an excellent, and extended, opportunity to participate in, and to observe, the causes and effects of this development. This involvement has made the writer keenly aware of the interaction between the traditional, rural-based agrarian society and culture found in Lesotho and trends in architectural development.